Lecturers’ Efficacy and Readiness towards Utilization of ICT for Academic Research in College of Education - Odefunsho, Olukayode Amos; Oladimeji, Rasheedat Modupe; Bolaji, Hammed Olalekan; Akinnubi, Olaolu Paul (Universitas Pendidikan Indonesia (UPI), 2023)
The study investigated Lecturers’ Efficacy and Readiness towards the Utilization of ICT for Academic Research in the College of Education in Kwara State. Non-experimental research design involving a descriptive survey was adopted. The instrument used for data collection was a questionnaire. The instruments were given to three experts in Science Education, Test, Measurement, and Evaluation. ICT experts who determined the validity of the instrument. The lecturers' Efficacy, lecturers' readiness, and lecturers utilizations were measured through a questionnaire. The population of the study was all the lecturers in the two Colleges of Education used as case studies comprising state and private colleges of education. The study also made use of 140 academic staff in both colleges of Education adopting Krejcie and Morgan, 1970 i.e. Kwara State College of Education, Ilorin (153 participants) while Kwara State College Of Arabic and Islamic Legal Studies Ilorin Kwara State (52 participants) Structured questionnaire titled: “Lecturers’ Efficacy and Readiness towards Utilization of ICT Questionnaire” (LERUQ) was used to elicit information. Descriptive statistics of the frequency and percentage were used to answer research questions while Pearson Product Moment Correlation (PPMC) was used to test the research hypotheses formulated in the study at a 0.05 level of significance. The findings showed most of the lecturers’ had positive reactions towards it, limited knowledge, and limited understanding.